1985
DOI: 10.1128/jb.161.3.1171-1175.1985
|View full text |Cite
|
Sign up to set email alerts
|

Purification of bromoperoxidase from Pseudomonas aureofaciens

Abstract: A Bromoperoxidase has been isolated and purified from Pseudomonas aureofaciens ATCC 15926 mutant strain ACN. The purified enzyme was homogeneous as determined by polyacrylamide gel electrophoresis and ultracentrifugation. This bromoperoxidase can utilize bromide ions in the presence of hydrogen peroxide and a halogen acceptor for the catalytic formation of carbon-halogen bonds. The homogeneous enzyme also has peroxidase and catalase activity. Based on the results from gel filtration and ultracentrifugation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…We attribute the BrPO activity to the diatoms rather than bacteria because (1) the number of bacterial cells per diatom cell in the nonaxenic cultures was extremely low, especially in the cultures of polar species; (2) there was no difference in halogenation rates between P. glacialis cultures in exponential and stationary phase, whereas the later phase showed an increase in bacterial numbers; (3) calculated rates of release based on bacterial cell surface area are extremely high and unrealistic (.600 mmol cm 22 h 21 ); and (4) P. glacialis cultured in the presence of antibiotics reduced the number of bacteria by 80%, compared to a culture without antibiotics, with only a 22% reduction in PR halogenation. It has been reported that the BrPO activity (units mg 21 of BrPO enzyme) from the freshwater bacterium Pseudomonas aureofaciens was at least four orders of magnitude lower than the activity of algal BrPOs (van Pee and Lingens 1985). If the bacteria in the diatom cultures were contributing to the bromination of PR, it would likely be at a very low level compared to the diatom contribution.…”
Section: Discussionmentioning
confidence: 98%
“…We attribute the BrPO activity to the diatoms rather than bacteria because (1) the number of bacterial cells per diatom cell in the nonaxenic cultures was extremely low, especially in the cultures of polar species; (2) there was no difference in halogenation rates between P. glacialis cultures in exponential and stationary phase, whereas the later phase showed an increase in bacterial numbers; (3) calculated rates of release based on bacterial cell surface area are extremely high and unrealistic (.600 mmol cm 22 h 21 ); and (4) P. glacialis cultured in the presence of antibiotics reduced the number of bacteria by 80%, compared to a culture without antibiotics, with only a 22% reduction in PR halogenation. It has been reported that the BrPO activity (units mg 21 of BrPO enzyme) from the freshwater bacterium Pseudomonas aureofaciens was at least four orders of magnitude lower than the activity of algal BrPOs (van Pee and Lingens 1985). If the bacteria in the diatom cultures were contributing to the bromination of PR, it would likely be at a very low level compared to the diatom contribution.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, it has also been shown that species of diatoms release HOBr and IOBr, which may react with extracellular DOM [Hill and Manley, 2009]. Although most widespread in eukaryotic organisms, bromoperoxidases, although generally with lower halogenating activity, have also been identified in bacteria, e.g., in Pseudomonas aureofaciens [Van Pée and Lingens, 1985], and it has been shown that cyanobacteria may produce halocarbons [Johnson et al, 2011;Karlsson et al, 2008;Schall et al, 1996]. So even if algae were the most likely producers of the halocarbons measured, it cannot be excluded that bacteria were partly responsible for the halocarbon production.…”
Section: Polar Mixed Layer In the Makarov Basin Over The Lomonov Ridmentioning
confidence: 99%
“…This could be due to the fact that these enzymes are prone to fast enzyme inactivation, along with other known issues such as no substrate specificity and non-regioselectivity. [83][84][85]…”
Section: Heme-iron-dependent Haloperoxidases From Natural Product Patmentioning
confidence: 99%